Making agreements in medieval Catalonia : power, order, and the written word, 1000-1200 - Kosto, Adam J. (Cambridge studies in medieval life and thought ;, 2001)
This study examines the role of written agreements in eleventh- and twelfth-century Catalonia, and how they determined the social and political order." "By tracing the fate of these agreements - or convenientiae - from their first appearance to the late twelfth century, it is possible to demonstrate the remarkable stability of the fluid structures that they engendered in what is generally thought of as "feudal society." The opportunity presented by these records to examine the process of documentary change reveals the true nature and pace of the "transformation of the year 1000." Analysis of the convenientia as an instrument of power and its interaction with oral practices contributes to a deeper understanding of the role of the written word in medieval societies. Finally, a broad historiographical context establishes the significance of this study of Catalonia for a more general appreciation of the medieval Mediterranean world. The book thus raises in a forceful way many of the questions most intensely debated by historians of medieval Europe.--Publisher description